Knowledge regarding adverse effects of selected cosmetic products among higher secondary level girl students, Chitwan - Shrestha, R; Shakya, J (Journal of Chitwan Medical College, 2017)
Cosmetics are substances used to enhance the appearance or odour of the human body. The age that females begin wearing makeup gets younger and younger with every new generation. A descriptive study design was used to find out knowledge regarding adverse effects of selected cosmetic products among higher secondary level girl students. A total 70 female students of Maiya Devi Girls’ College, Bharatpur-10, Chitwan, 34 students of grade 11 and 36 students of grade 12 were selected by using probability simple random sampling lottery method. The result revealed that out of 70 respondents, 30% were of age 17 years, 51.4% were studying in grade 12. 34.3% respondents’ had experienced adverse effects from using cosmetic products, 50% had experienced acne, almost all respondent’s 98.6% got information of cosmetic products from television. Majority 82.9% of the respondents answered that cosmetic products are the substance use to enhance the appearance of body. Cent percent respondents’ had knowledge that lipstick cause lip cancer, 88.6% had knowledge that kajal cause dry eye syndrome, 97.1% had knowledge that skin lightening cream and sunscreen cause skin cancer and perfumes cause skin irritation, 87.1% had knowledge that mascara cause eye irritation, and 98.6% had knowledge that nail polish cause cancer and reading expiry and manufacture date can prevent the occurrence of adverse effects. Majority 72.9% of respondents had average level of knowledge, 17.1% had low level of knowledge and 10.0% had high level of knowledge. Statistically there was significant association between level of knowledge of the respondents’ regarding adverse effects of selected cosmetic products and grade of respondents (p = 0.044).